Performances assessment of Anipill® device prototype designed for continuous temperature monitoring. (20th August 2018) - Chapon, Pierre-Alexandre; Bulla, Jan; Besnard, Stéphane; Gauthier, Antoine; Bessot, Nicolas
Abstract: This study aimed to test the validity and reliability of the latest version of the Anipill ® device including a calibration assessment step and an in-vivo testing in rodents. After performing a calibration procedure, 10 rats were intraperitoneally implanted with a pair of sensors, one Anipill ® (8.2 mm diameter, 17.2 mm length) and one Jonah ® (8.7 mm diameter, 23 mm length). Temperature data were collected and compared during both a 24 h period of free ranging and after an injection of Lipopolysaccharide d' Escherichia coli, serotype 0111:B4 (LPS) and Apomorphine hydrochloride. Furthermore, the transmission distance of Anipill ® was assessed by moving the animal compound away from the data logger. The results of the calibration process indicate a significant average difference between Anipill ® and Jonah ® of .04 ± .04 °C. During free ranging, the mean inter-sensors difference observed was −.1 ± .1 °C. Nevertheless, the instantaneous difference values between devices could sometimes reach .96 °C (.2 < 90% interquantile range <1.1 °C). Concerning the pharmacological effect periods, the mean difference observed was −.01 °C ± .1 °C during the Apomorphine phase and −.09 °C ± .08 °C during the LPS phase. However, the instantaneous difference values between devices could sometimes reach .6 °C (.2 < 90% interquantile range <1.2 °C) and .7 °C (.3 < 90% interquantile range <.8 °C) during Apomorphine and LPS phases respectively. The observed differences exceeding 1 °C cannot wholly be explained by the sensors' variability but rather by animal physiology. Concerning the transmission distance assessment, 48% of the data were still collected when the distance between the animal and the Anipill® receptor reached 5 m. Anipill® possesses some advantages against Jonah, notably a greater transmission distance and battery life, and a self-memory.